Nesting-induced local electronic patterns around a single As (Te, Se) vacancy in iron-based superconductors - Degang Zhang; Zhihai Liu; Jianming Ma; Jiangshan Liu; Zhengwei Xie; C S Ting (New Journal of Physics, 2018)
The local electronic states around a single As (Te, Se) vacancy are investigated in order to shed light on the role of ligands in a series of iron-based superconductors. Such a vacancy can produce a local hopping correction ranging from −0.22 to 0.12 eV and always induce two in-gap resonance peaks in the local density of states (LDOS) at the fixed symmetrical bias voltages, which are rather robust and irrelevant to the phase of superconducting order parameter. The LDOS images near the defect predominantly possess 0° and 45° stripes. These energy-dependent charge modulations created by quasiparticle interference are originated in the nesting effect between the inner (outer) hole Fermi surface around Γ point and the inner (outer) electron Fermi surface around M point.